Big Five traits as predictors of perceived stressfulness of the COVID-19 pandemic. (June 2021) - Zacher, Hannes; Rudolph, Cort W.
Abstract: This study examined the Big Five personality traits as predictors of individual differences and changes in the perceived stressfulness of the COVID-19 pandemic in Germany between early April 2020 and early September 2020. This timeframe includes the first national "lockdown, " the period of "easing" of restrictions, and the summer vacation period. Data were collected from n  = 588 full-time employees, who provided baseline data on their personality traits in early December 2019, and then later provided data on perceived stressfulness of the COVID-19 pandemic at five time points, spanning six months. Consistent with expectations based on event and transition theories, results showed that, on average, perceived stressfulness declined between early April 2020 and early September 2020. Moreover, this effect was stronger between early April 2020 and early July 2020. Hypotheses based on the differential reactivity model of personality and stress were partially supported. Emotional stability was associated with lower, and extraversion associated with higher, average levels of perceived stressfulness. Finally, extraversion was associated with increases (i.e., positive trajectories) in perceived stressfulness between early April 2020 and early July 2020 and decreases (i.e., negative trajectories) in perceived stressfulness between early July 2020 and early September 2020.